Polipoidalna waskulopatia naczyniówkowa – rzadka postać neowaskularyzacji naczyniówkowej - Węglarz, Monika; Karska-Basta, Izabella; Kubicka-Trząska, Agnieszka; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Purpose: To present two cases of polypoidal choroidal vasculopathy (PCV). Material and methods: Two 85- and 76-years old female patients were enrolled in the study. One patient was referred to the Ophthalmology Clinic in Krakow with the presumptive diagnosis of the choroid tumor in the left eye. The other one was suspected of choroidal neovascularization (CNV) in the course of age-related macular degeneration (AMD) in the left eye. Both patients underwent the basic ophthalmic examination, fluorescein (FA) and indocyanine green (ICGA) angiography. Additionally ocular ultrasonography and MRI of the head and orbits were performed in the patient suspected of the choroid tumor. Results: Performed investigations, especially the results of ICGA allowed to establish the definitive diagnosis of polypoidal choroidal vasculopathy in both cases. Conclusions: Our study shows potential diagnostic difficulties occurring in patients with PCV and indicate ICGA as the method of choice confirming the diagnosis.